Risk Factors for Adverse Maternal Outcomes following Expectantly Managed Preterm Prelabor Rupture of Membranes - Darling, Alice J.; Harris, Hailey M.; Zemtsov, Gregory E.; Small, Maria; Grace, Matthew R.; Wheeler, Sarahn; Dotters-Katz, Sarah K. (American Journal of Perinatology, 2021)
Objective We sought to characterize the incidence and risk factors associated with developing maternal morbidity following preterm prelabor rupture of membranes.Study Design Retrospective case–control study of patients with preterm prelabor rupture of membranes at a single institution from 2013 to 2019 admitted at ≥23 weeks gestational age. The primary outcome was a composite of maternal morbidity which included: death, sepsis, intensive care unit (ICU) admission, acute kidney injury, postpartum dilation and curettage, postpartum hysterectomy, venous thromboembolism, postpartum hemorrhage, postpartum wound complication, postpartum endometritis, pelvic abscess, postpartum pneumonia, readmission, and/or need for blood transfusion were compared with patients without above morbidities. Severe morbidity was defined as: death, ICU admission, venous thromboembolism, acute kidney injury, postpartum hysterectomy, sepsis, and/or transfusion >2 units. Demographics, antenatal, and delivery characteristics were compared between patients with and without maternal morbidity. Bivariate statistics and regression models were used to compare outcomes and calculate adjusted odd ratios.Results Of 361 included patients, 64 patients (17.7%) experienced maternal morbidity and nine (2.5%) had severe morbidity. Patients who experienced maternal morbidity were significantly (p < 0.05) more likely to be older, have private insurance, have BMI ≥40, have chorioamnionitis at delivery, and undergo cesarean or operative vaginal delivery when compared with patients who did not experience morbidity. After controlling for confounders, cesarean delivery (aOR 2.38, 95% CI[1.30,4.39]), body mass index ≥40 at admission (aOR 2.54, 95% CI[1.12,5.79]), private insurance (aOR 3.08, 95% CI[1.54,6.16]), and tobacco use (aOR 3.43, 95% CI[1.58,7.48]) were associated with increased odds of maternal morbidity.Conclusion In this cohort, maternal morbidity occurred in 17.7% of patients with preterm prelabor rupture of membranes. Private insurance, body mass index ≥40, tobacco use, and cesarean delivery were associated with higher odds of morbidity. These data can be used in counseling and to advocate for smoking cessation.Key Points
Keywords: maternal morbidity; PPROM; tobacco use; preterm; cesarean delivery